2019
DOI: 10.22435/bpk.v47i4.1861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pengendalian Schistosomiasis oleh Lintas Sektor Tahun 2018

Abstract: Abstract In Indonesia, schistosomiasis is caused by Schistosoma japonicum with Oncomelania hupensis lindoensis as the intermediate host. Schistosomiasis can infect humans and all species of mammals. In order to achieve schistosomiasis elimination by 2020, schistosomiasis control including environmental management, has been carried out by multi-sectors. A cross-sectional study was conducted in 2018 to evaluate multi-sectoral schistosomiasis control programs. Data were collected by in-depth interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
3
1
2
Order By: Relevance
“…This outcome is dissimilar from a previous study (2010) which failed to find S. japonicum infection in 90 animals examined (19 dogs, 55 pigs, one horse, three buffaloes, and 12 cattle) (Rosmini et al 2014). Another survey did not find S. japonicum infection in animals in Lengkeka, Kageroa, Tuare, and Tomehipi villages, with samples of 17, 14, 30, and 31, respectively (Anastasia et al 2019). The result variations may be due to the different number of samples in collection time and examination methods.…”
Section: Resultscontrasting
confidence: 73%
“…This outcome is dissimilar from a previous study (2010) which failed to find S. japonicum infection in 90 animals examined (19 dogs, 55 pigs, one horse, three buffaloes, and 12 cattle) (Rosmini et al 2014). Another survey did not find S. japonicum infection in animals in Lengkeka, Kageroa, Tuare, and Tomehipi villages, with samples of 17, 14, 30, and 31, respectively (Anastasia et al 2019). The result variations may be due to the different number of samples in collection time and examination methods.…”
Section: Resultscontrasting
confidence: 73%
“…Due to the difficulty of obtaining stool specimens, community participation in stool collection is low. The role of related cross-sectors has not been maximized, as evidenced by research conducted by the Donggala Health Research and Development Center, which revealed that 53.6% of the activities outlined in the roadmap were not carried out in 2018 [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all the roles or responsibilities of each ministry have been carried out based on the target. The results of research that evaluated the cross-sectoral activities stated the activities carried out were only about 58% [15]. It is necessary to strengthen efforts to accelerate the achievement of schistosomiasis elimination targets, namely re-mapping of cross-sectoral roles in the integration of schistosomiasis elimination interventions, Community Empowerment Improvement (Bada Model Replication in other endemic villages, Gema Beraksi, and Gadar Basis), utilization of financing sources (State Budget, Local Government Budget, and Village Budget) to support community empowerment based on the schistosomiasis control program, capacity building for laboratory personnel through training/internships at the Health Research and Development Center, strengthening the role of R&D in the development of research in policy-making with a socio-anthropological approach and procedures for surveillance, monitoring and evaluation of the elimination of schistosomiasis in animals, and mapping of risk factors in other animals, as well as strengthening the role of district governments in planning and financing Schistosomiasis Control (Master Plan, Regent Regulation) [3].…”
Section: Discussionmentioning
confidence: 99%
“…dilakukan hingga saat ini belum dapat menekan angka kejadian schistosomiasis, karena adanya reinfeksi dari berbagai reservoar diantaranya tikus, ternak masyarakat, termasuk hewan liar, bahkan masyarakat sendiri sebagai pembawa. Salah satu masalah yang dihadapi dalam dalam program pengendalian schistosomiasis adalah pengendalian keong dan daerah fokus tidak dilakukan secara komprehensif dan 3,9 teratur di daerah endemis.…”
Section: Pendahuluanunclassified